2019
DOI: 10.1021/acschembio.9b00585
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic Delivery of Macromolecules in Live Human Cells Using the Combined Endosomal Escape Activities of a Small Molecule and Cell Penetrating Peptides

Abstract: Ineffective cellular delivery is a common problem in numerous biological applications. Developing delivery reagents that work robustly in a variety of experimental settings remains a challenge. Herein, we report how peptides derived from the prototypical cell penetrating peptide TAT can be used in combination with a small molecule, UNC7938, to deliver macromolecules into the cytosol of cells by a simple co-incubation protocol. We establish successful delivery of peptides, DNA plasmids, and a single-chain varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 42 publications
1
38
0
Order By: Relevance
“…Thus, cytosolic delivery of the Bax-BH3 peptide should enable this function. However, this 20-amino acid peptide is impermeable to cells, for which its effective delivery requires direct injection into this compartment [ 43 , 44 , 45 ]. Hence, this example can also serve to verify whether active cargo can be delivered to the cytosol by PZ polymers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, cytosolic delivery of the Bax-BH3 peptide should enable this function. However, this 20-amino acid peptide is impermeable to cells, for which its effective delivery requires direct injection into this compartment [ 43 , 44 , 45 ]. Hence, this example can also serve to verify whether active cargo can be delivered to the cytosol by PZ polymers.…”
Section: Resultsmentioning
confidence: 99%
“…Following entry into cells by endocytosis, protein delivery systems are often retained in the endo-lysosomal compartment and cannot escape into the cytosol to traffic to or reach other intracellular targets [ 2 , 5 , 8 , 24 , 45 ]. With regard to the subsequent endo-lysosomal trafficking of internalized PZ complexes, we again saw a difference in the kinetics of the process between the two polymers, with the PZ-PYR/FITC-avidin trafficking rapidly to the lysosomal compartment, as evidenced by a low colocalization with endosomes at 1 h or 5 h, while their localization with lysosomes was slightly higher compared to endosomes and sustained over this time ( Figure 5 A,B).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the OEC seems to act at a site in the trafficking pathway that is after early endosomes, but before lysosomes, probably within the key MVB/LE compartments that are the natural sites of productive oligonucleotide release to the cytosol [ 4 , 33 ]. Additional reinforcement regarding the site of action of OEC UNC7938 comes from a recent study that demonstrated that this compound binds preferentially to lysobisphosphatidic acid, a lipid found predominately in MVBs [ 71 ]. Thus, the UNC7938 and UNC2383 OECs have many interesting and valuable characteristics as modulators of oligonucleotide release from endosomes and are currently being explored for possible therapeutic use.…”
Section: Manipulation Of Oligonucleotide Delivery and Effect Using Small Moleculesmentioning
confidence: 99%
“…The conjugates were tested in a luciferase reporter gene assay with the well-known splice switching ON sequence SSO 623 [ 176 ] in HeLa Luc 704 cells. Unfortunately, none of the novel conjugates afforded an improvement in splice-switching activity over the dual use of SSO 623 with UNC7938 as a widely used endosome-destabilizing agent [ 344 , 346 ] or even SSO 623 alone. The reasons for this have not been elucidated yet, but ongoing research attempts to use more potent analogues of Retro-1 [ 344 , 347 ] or variations of spacer units to overcome possible impairments with the splice-switching machinery.…”
Section: Conjugation Of On With Small Molecules For Enhanced Endosmentioning
confidence: 99%